Livestock research for development in a complex, messy world: Reflexions on a decade of work for ILRI - Seré Rabé, Carlos (International Livestock Research Institute, 2011)
Speech by former Director General Carlos Seré at the liveSTOCK Exchange, Addis Ababa 9-10 November 2011.